A framework for accident reduction and risk identification and assessment in Saudi Arabia. Issue 3 (29th July 2014) - M. Al-Atawi, Attiyah; Kumar, Ravindra; Saleh, Wafaa
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a framework methodology for the assessment and improving accident data collection and analysis in the Kingdom of Saudi Arabia (KSA). Design/methodology/approach – A proposed framework methodology for accident reduction by an integrated process which includes a risk identification, assessment and reduction process is proposed for Tabuk city in KSA. Findings – Tabuk city has a high accident rate. The proposed framework can improve the process of accident data collection and analysis and identify hot spot locations and accident severity. Originality/value – It has been estimated that the annual cost of traffic accidents in Saudi Arabia exceeds six billion US dollars, in addition to other social, health and economic impacts, such as disability, rehabilitation and unemployment due to traffic accident injuries. There are not many studies, if any, in Tabuk in KSA on the investigation and development of a framework for accident reduction.